“PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN PEMAIN CLUB SEPAK BOLA LPHR ( LASKAR PATIH HARIMAU ROKAN ) TALIKUMAIN KABUPATEN ROKAN HULU” - Okto Vernanda, Oriza Sativa; Zainur, Zainur; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstark: The problem in this research is that their athletes are very good technically, but what becomes a problem when the athlete is training or competing in competitions is that the athlete's stamina is very low. The aim of this research is that athletes can perform and play much better and especially after examination and find out if there is an increase in their endurance so that they can play for a long time. Design reacserch of this research is (using a one-group pre-test-post-test design approach) with the population of the LPHP football club (Laskar Patih Harimau Rokan). The data in this research was the full population of 18 people. The tool used in this research was the use of the beep test, which aims to determine your stamina strength. Then the data was statistically processed to test for normality using the Lilifours test at a significant level of 0.05α. Based on the analysis of the normality test data, X produces a LoMax of 0.142 and an L table of 0.200, which means that LoMax <L table. while variable Y produces LoMax of 0.154 and Ltable of 0.200. This means that LoMax <L The data table is normally distributed. Furthermore, when testing the t-distribution, the goal is to determine the effect of variable x and variable y, the value of t = 5,600 is obtained, then tcount> ttable is (5,600)> (1,740), then Ha accepted, in other words there is an effect of interval training on the endurance of club players. football LPHR (laskar patih tiger rokan) Talikumain, Rokan Hulu Regency.Key Words: Interval Training, Endurance, Football